CCNP routing and switching SWITCH 300-115 complete video course - Wallace, Kevin, 1965-; Safari eBooks ([Place of publication not identified] : Pearson Certification, 2015)
"CCNP Routing and Switching SWITCH 300-115 Complete Video Course is a comprehensive training course that brings Cisco CCNP R&S SWITCH exam topics to life through the use of real-world demonstrations, animations, live instruction, and configurations, making learning these foundational networking topics easy and fun. Best-selling author, expert instructor, and double CCIE Kevin Wallace walks you through the full range of topics on the CCNP Routing and Switching SWITCH 300-115 exam, including Cisco Catalyst switch features, VLANs and trunking, Spanning Tree Protocol (STP), EtherChannel technologies, first hop redundancy protocols, and securing Cisco Catalyst switches. This unique product contains multiple types of video presentations, including live instructor whiteboarding, real world demonstrations, animations of network activity, dynamic KeyNote presentations, doodle videos, and hands-on router and switch CLI configuration and troubleshooting in real lab environments, allowing you to both learn the concepts and the hands-on application."--Resource description page.
Title from resource description page (viewed February 4, 2015)
Date of publication taken from resource description page.
On-screen presenter, Kevin Wallace.
Keywords: Computer networks -- Management -- Examinations -- Study guides; Routing (Computer network management) -- Examinations -- Study guides; Switching circuits; Cisco career certification; Electronic books